The Effect of Long Term Use of Combined Pills and Depo-Provera on Bone Density Parameters - Al- Omari, Wafa; Al- Shammaa, Haider B.; Al-Obaidy, Nagham A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Promotion of bone health is particularly important for young women at reproductive age group, as the critical years for building bone mass are from pre-adolescence to about age 30 years.patients and Methods: This cross sectional study was performed on three groups, first group of 30 women who had used combined pills for more than 2 years, second group of 30 women who had used Depo-Provera for more than 2 years, last group contain 30 women who had used barrier method or they didn’t use any contraceptive as a control group.Bone mineral density (BMD) of lumbar spine (L2-L4), right proximal femur was determined by dual energy x-ray absorptiometry in (femoral neck, greater trochanter, ward’s triangle, and shaft of femur). Evaluation of serum calcium was performed. Results: The results of three groups were compared to predict the influence of using hormonal contraceptive measures on bone mineral density. The study showed significant increase in BMD among women using combined pills, and decrease in BMD among women using Depo-Provera in all anatomical sitesConclusions: The use of combined pills protects or increases BMD, while Depo-Provera diminishes BMD. In essence, improving BMD While using combined pills can be regarded as one of the benefits of this method.